Five essential lessons in antimicrobial stewardship and leadership I have learned from running - Miranda So (Antimicrobial Stewardship & Healthcare Epidemiology)
As an antimicrobial stewardship pharmacist and an avid runner, I identified the five essential lessons I have learned from running that are transferrable to implementing initiatives, conducting practice-based research and leading an antimicrobial stewardship program. To ensure this commentary will resonate with the reader, I provided an illustrative example connecting each lesson from running with a transferrable concept or practice in antimicrobial stewardship.